Utilization of palm oil waste as bioenergy - Amalia Murnihati Noerrizki; Tresna Kusuma Putri; Ernah Ernah (Sustinere: Journal of Environment and Sustainability, 2019)
Palm oil is one of the most widely produced plantation commodities in the world. World demand for palm oil is also increasing due to the increasing demand for products that use palm oil. This increase ultimately results in the development of the palm oil processing industry which causes the increasing volume of waste produced. Palm oil waste can be utilized and treated as bioenergy so as to add economic value to the waste. The purpose of this paper is to determine the benefits of palm oil waste as bioenergy. The results show that palm oil waste such as shells, empty fruit bunches of palm, fibers, leaves, midribs and Palm Oil Mill Effluent (POME) have several potential contents to be utilized as bioenergy such as biogas, biodiesel, biobriquette, electricity generator, and activated charcoal. Apart from that as bioenergy, palm oil waste can be used as an antioxidant, animal feed, fertilizer and concrete additives.